Valgretsdebattens vitale stemmer - Et offentlighedsperspektiv - Fiig, Christina (Slagmark - Tidsskrift for idéhistorie, 2018)
This article approaches the struggles for enfranchisement within a perspective of a public sphere as conceptualized by Jürgen Habermas and Nancy Fraser. It focuses on one Danish suffragette organisation and its membership magazine, Kvindevalgret (1908-1915), as an exemplification of a type of opinion-forming public. In so doing the article is informed by the assumption that this type of public is a central democratic arena in which the process of deliberation has intrinsic value. The case demonstrates how participants in such a public can use a public arena as a means of politicising their situation, of democratic learning and of constructing political identities – in this case as mature, capable female voters. This was a controversial identity formation in the historical period of strong Conservative forces. The suffragettes’ in the debate were inspired by the contemporary philosophy of John Stuart Mill, in particular his liberal and utilitarian thinking on women as mature adults and as contributors to society’s well being.